Pola Asuh Orangtua terhadap Perilaku Konsumtif Remaja Penggemar KPOP - Zahra Ziadhatun Nisa; Dian Alfia Purwandari; Sujarwo Sujarwo (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The phenomenon of globalization is the development of kpop culture which then forms kpop fans dominated by teenagers who tend to do consumptive behavior. Parenting styles is one of the factors that can influence consumptive behavior in children. This study aims to determine the relationship between parenting style and consumptive behavior of adolescent kpop fans at SMP Negeri 92 Jakarta. The method used was quantitative with a sample of 47 teenage kpop fans, sampling using purposive sampling techniques. The results showed that there is a relationship between parenting styles and the consumptive behavior of teenagers who are kpop fans at SMP Negeri 92 Jakarta.